Serum connexin 26 as a potential marker of non-syndromic hearing loss - Hend M. Moness; Noha M. Abdullah; Doaa El Amrousy; Reham Gamal; Hatem A. Mohamed; Mohammed A. Gomaa; Shaimaa Moustafa Hafez; Zamzam Hassan Mohamed (The Egyptian Journal of Otolaryngology)
Abstract Background Hearing loss (HL) represents the most common form of sensory impairment in both children and adults. In children, genetic causes account for over 50%. The genetic causes of HL include multiple syndromes associated with HL. In non-syndromic hearing loss (NSHL), patients have only hearing impairment or loss. 35delG, 167delT are common mutations that lead to severe HL. The prevalence of these mutations varies according to region, population characteristics, and within the same region according to the genetic pools. There is currently no approval for laboratory investigations to diagnose non-syndromic hearing loss (NSHL) except few studies that are based on expensive genetic tests. This study evaluates the value of connexin 26 as a screening test for NSHL. Methods One hundred forty children participated in our study; they were divided into two groups. Seventy children with NSHL and 70 children as control group. All children were subjected to Audiometry, measurement frequency of 35delG, 167delT by PCR–RFLP, and connexin26 level by ELISA. Results We found that the connexin 26 level by ELISA was significantly lower in patients compared to controls (p = 0.0001). In addition, there was a significant negative correlation between connexin 26 levels and the degree of hearing loss by audiometry (r = − 0.403, p < 0.0001). In ROC curve analysis, serum levels of connexin 26 have sensitivity (94.3%) and specificity (100%). Measuring of connexin 26 by ELISA is more sensitive and specific than 35 del G mutation where sensitivity was 11.45 and 5.7% for both hetero and homo mutation. Conclusion Serum connexin 26 could be used as a good diagnostic marker to detect NSHL in children. It could be used as a potential marker for NSHL in newborns as it is more rapid and easily available than genetic study, especially in developing countries.